2019
DOI: 10.1002/cptc.201900019
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Uptake of Diarylethene‐Based Cell‐Penetrating Peptides into Cells Using Light

Abstract: We report on diarylethene (DAE)‐containing photoswitchable cell‐penetrating peptides (CPPs) capable of photocontrolled cell entry. We demonstrate in vitro that reversible photoisomerization of a DAE fragment in the backbones of non‐cytotoxic cyclic peptides influences their binding to cell membranes and subsequent CPP‐mediated cargo internalization. Benign red light can be used to activate cell entry of our compounds. We suggest that the observed differences in cell uptake of the two photoisomers are due to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…62A ). 695 Upon irradiation with light and formation of the more rigid C isomer, the hydrophobicity decreases and significantly deviates from the original CPP, therefore hindering cellular uptake. Additionally, the CPP was modified with fluorescein, attached via a long linker to minimize the effect of the large fluorescent organic molecule on permeability ( Fig.…”
Section: Illustrative Examples Of Photoswitches In Aqueous Mediamentioning
confidence: 99%
“…62A ). 695 Upon irradiation with light and formation of the more rigid C isomer, the hydrophobicity decreases and significantly deviates from the original CPP, therefore hindering cellular uptake. Additionally, the CPP was modified with fluorescein, attached via a long linker to minimize the effect of the large fluorescent organic molecule on permeability ( Fig.…”
Section: Illustrative Examples Of Photoswitches In Aqueous Mediamentioning
confidence: 99%
“…An additional benefit of this system is that the inactive form of 160 lacks the hemolytic side effect for which gramicidin is notorious, offering the potential for more selective antimicrobial treatments. Finally, Komarov and co-workers also demonstrated that the diarylethene moiety can be used to switch a cyclic peptide scaffold between membrane permeable/impermeable states, 378 a notable contrast which was attributed to a difference in the flexibility of the two photostates.…”
Section: Side Chain−side Chain Cross-linksmentioning
confidence: 99%
“…The Ulrich group designed circular ACPPs consisting of a peptide fragment of 9 to 14 residues, with a charge between +4 and +10, and a photoswitchable diarylethene (DAE) group ( Table 4 , entry 6). 70 DAE is a rigid structure that becomes flexible upon irradiation with visible light ( λ = 590 nm), while irradiation with UV-light brings the DAE to its rigid form. The rigid DAE imposed a non-optimal structure for the circular ACPP thereby preventing it from entering the cell.…”
Section: Cpp Activation Through An Induced Conformational Changementioning
confidence: 99%